Design and analysis of flour sieving machine prototype using autodesk inventor - Ismail, Mohd Erfy; Razali, Nizamuddin; Hashim, Suhaizal; Masek, Alias; Ismail, Irwan Mahazir (2022)
Small and Medium Industries (SMIs) significantly contribute to the country, especially in the Gross Domestic Product (GDP), employment, and exports. However, with the challenging external environment, SMIs must innovate to compete and survive in the business environment. Several problems can be identified in this study, such as the need to save on energy consumption and workers when operating the original Flour Sieving Machine, less productivity due to machine size, and the safety issue when the machine works at the exceeded limit of 2 kilograms (kg).Caused by that, this study aims to reduce the use of energy and labor, innovate the machine to the ideal or suitable size to save production time, and improve the safety aspects of machine operation for the safety of users and a longer life-span for the machine to operate. Therefore, researchers have conducted observations and discussions with the industry to identify and determine the elements of problems in the operation of Flour Sieving Machine through the House of Quality (HOQ) method. Next, the researchers used the information obtained from the HOQ matrix evaluation to design and innovate a new Flour Sieving Machine using Autodesk Inventor 2016 software. One of the innovations is changing the semiautomatic system to an automatic system, i.e., the press paddle to the adjusting switch, to reduce energy and labor in operating the Flour Sieving Machine. Another innovation made is increasing the width of the machine frame and flour sieve container. Apart from saving time, it can also accommodate 5 kg of flour in one sieving process compared to the original machine with only 2 kg of flour. The machine's safety characteristics may then be addressed after increasing the width of the machine's size because the machine can sustain a greater load than the original machine, making the innovation machine more durable to use in the long term. All these innovations are analyzed and simulated to obtain a new optimal Flour Sieving Machine design. The researchers discovered that the design of the Innovation Flour Sieving Machine could solve the problem of SMIs in terms of saving energy, manpower, and time, increasing the amount of flour that can be sieved at one time and increasing the comfort and safety of users and machines because the innovation machine can accommodate a larger load than the original machine as a result of the simulation. It can be concluded that there are some improvements in quality, productivity, and safety during the operation of this Innovative Flour Sieving Machine.